Man and Woman: the Last Obstacle for Boolean Coordination - Champollion, Lucas (Proceedings of the Amsterdam Colloquium, 2013)
The word and can be used both intersectively and collectively. A major theme in research on coordination has been the quest for a lexical entry that uni es these uses, either based on boolean intersection or based on collective formation. Focusing on English noun noun coordination, this paper argues for the boolean option. This immediately delivers the intersective behavior of and, as in liar and cheat; as for its collective behavior, as in man and woman, it falls out of the interaction of and with a series of independently motivated type shifters, mainly taken from Winter (2001). Such coordinations are interpreted collectively because the two nouns are interpreted in the same way as the DPs in a man and a woman.